Transforming School Culture into Character-Building Ecosystem: Integrating the Pancasila Student Profile and Rahmatan Lil ’Alamin - Nikmah, Yuliatun; Salisah, Zahrotus; Zainuri, Zainuri (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2025)
The integration of the Pancasila Student Profile with Rahmatan Lil ’Alamin values is considered strategic for fostering holistic character, combining the nation’s ideological foundation with universal religious values. This study explores the transformation of school culture into a character-building ecosystem through the integration of the Pancasila Student Profile and Rahmatan lil ’Alamin values. By combining the ideological foundation of Pancasila with universal Islamic teachings, the school implements character education programs encompassing routine religious activities and contextual learning practices. Employing a qualitative descriptive approach, the research was conducted through observation, interviews, and documentation to examine the effectiveness of program implementation. The findings indicate that, despite challenges such as limited facilities and infrastructure, SMP Ma’arif 1 Ponorogo has successfully developed a supportive learning environment that fosters students’ moral integrity, inclusiveness, and holistic character. This study emphasizes the significance of integrating national and religious values in school culture as a sustainable strategy to cultivate quality learners who are not only rooted in local wisdom but also prepared to face global challenges. However, this study is limited by its qualitative scope, focusing only on a single school context, which may restrict the generalizability of the findings. Future research is recommended to involve broader samples and mixed methods to provide more comprehensive insights.